REPRESENTATION OF ACTORS IN CHILDREN STORIES: A CRITICAL DISCOURSE PERSPECTIVE - Vitananda, Delia (2015)
This study examines the representation of social actors in children stories. More specifically, it explores (1) how the social actors are represented in the texts and (2) what the representations of social actors signify. Two folktales entitled The Ugly Duckling and The Little Matchgirlwritten by Hans C. Andersen were chosen as the data of this study. This study uses the theories of categorization of social actors (van Leeuwen, 2008) and transitivity (Halliday, 2004) as the bases of analysis. The findings show that all the social actors in the stories were mostly represented in inclusion, more specifically in Activation-Participation-Personalization. In addition, material process is mostly used in representing the social actors in the stories; consequently, actor is found to be the most frequent participant. Those results indicate that the social actors mostly actively participated in physical action and were treated as human beings. Finally, the study shows that representation can explore how the actors are constructed. Keywords: Representation, Children stories, Critical Discourse Analysis,Categorization of Social Actors, Transitivity Penelitianinimembahasrepresentasidariaktor-aktorsosialdalamceritaanak, khususnya, meneliti (1) bagaimanaaktor-aktorsosialdirepresentasikan di dalamteksdan(2) apamakna yang ditunjukkanolehrepresentasidariaktor-aktorsosial. Duaceritarakyat yang berjudulThe Ugly DucklingdanThe Little Matchgirlyang ditulisoleh Hans C. Andersen dipilihsebagai data daristudiini. Studiinimenggunakanteoritentangkategorisasiaktorsosial (van Leeuwen, 2008) dantransitivity (Halliday, 2004) sebagai basis analisis. Temuanpenelitianinimenunjukkanbahwasemuaaktorsosial di dalamceritahampirsemuadirepresentasikan di kategoriinclusion, lebihkhususlagi di kategoriAktivasi-Partisipasi-Personalisasi. Selainitu, proses material di transitivitysebagianbesardigunakandalammerepresentasikanaktorsosial di dalamcerita; olehkarenaitu, aktormerupakanpartisipan yang paling seringmuncul. Hasiltemuantersebutmenunjukkanbahwaaktor-aktorsosialhampirsemuaberpartisipasisecaraaktifdalamtindakanfisikdandiperlakukansebagaimanusia. Studiinimenunjukkanbawarepresentasidapatmenelaahbagaimanaaktor-aktordibangun di dalamcerita. Kata kunci: Representasi, ceritaanak, Critical Discourse Analysis, kategoriasasiaktorsosial, transitivity.